Regulating the crosstalk between Bifidobacterium and the brain: a potential therapeutic strategy for Alzheimer’s disease - Peng, Liting; Zhang, Zhiming; Hu, Yuan; Chen, Huijia; Tian, Yingru; Ling, Hongyan (Frontiers in Immunology, 2026)
Alzheimer’s disease (AD) is a common dementia in the elderly population, typically manifested through symptoms of cognitive impairment (CI) and memory loss. Pathologically, it is characterized by abnormally elevated levels of amyloid-β (Aβ) deposition and tau phosphorylation. Given the rapid rate of population aging, many scientists are investigating AD, focusing on its pathogenic mechanisms and potential treatments. Unfortunately, to date, no highly effective therapeutic strategies have emerged. Intriguingly, multiple studies have revealed alterations in the gut microbiome of individuals with AD, suggesting it may serve as a novel avenue for investigating AD pathogenesis. Bifidobacterium, a pivotal probiotic in the gastrointestinal tract, is crucial in upholding the equilibrium of gut flora. Notably, marked deficiencies in Bifidobacterium have been observed in the guts of AD patients, underscoring the potential of further inquiry into the impact of Bifidobacteria on AD via the gut-microbe-brain axis. However, current research on the mechanisms through which Bifidobacteria can alleviate AD is limited, warranting further investigation. This review examines Bifidobacterial alterations in Alzheimer’s disease patients and the underlying mechanisms, with the aim of evaluating their potential as a therapeutic strategy for Alzheimer’s disease.